2020
DOI: 10.29333/ejgm/7880
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Composition and Anthropometric Measurement with Hypertension among Workers in Universitas Ahmad Dahlan

Abstract: Purpose: This study aims to investigate the relationship between anthropometric and body composition measurement with the risk of hypertension among office workers. Methodology:This study was a cross-sectional study in office workers population in Universitas Ahmad Dahlan. The subjects of the study were 125 persons (72 males and 53 females) aged 20 -60 years. The measurement of anthropometry was using an electronic digital scale for weight, microtoise for height, and meter line for waist circumference. In anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The detail of the instrument can be seen in table 1 below. Each of the exercise methods has been previously validated for reliability in separate studies [47]. Test-retest reliability scores for each instrument revealed very good consistency with MFT, r=0.88; sit and reach test, r=0.89; sit up and push up, r=0.94 and r=0.95 respectively; leg and back dynamometer, r=0.90; and Omron karada scan body composition, r=0.99.…”
Section: Methodsmentioning
confidence: 94%
“…The detail of the instrument can be seen in table 1 below. Each of the exercise methods has been previously validated for reliability in separate studies [47]. Test-retest reliability scores for each instrument revealed very good consistency with MFT, r=0.88; sit and reach test, r=0.89; sit up and push up, r=0.94 and r=0.95 respectively; leg and back dynamometer, r=0.90; and Omron karada scan body composition, r=0.99.…”
Section: Methodsmentioning
confidence: 94%
“…BMI is categorized into two categories, normal and abnormal (underweight and obese), according to the classification of the nutritional status of Indonesians by the Ministry of Health of the Republic of Indonesia, where the nutritional status is underweight if the BMI <18.5 kg/m 2 , 18.5-25.0 kg/m 2 is normal, and obese if the BMI value is >25.0 kg/m 2 . 15 Psychosocial Stress Assessment Instrument (IPSP) used to measure level of stress psychosocial. This questionnaire consists of 35 events experienced during the last six months and one additional blank item (number 36) if there is another event that participants can mention themselves.…”
Section: Methodsmentioning
confidence: 99%
“…The sum of the scores is interpreted into seven categories. These categories are: not experiencing stress (0); experiencing low or little stress (1)(2)(3)(4)(5)(6)(7)(8); being mild stress (9)(10)(11)(12)(13)(14)(15)(16); moderate stress (25)(26)(27)(28)(29)(30)(31)(32)(33); high stress (25)(26)(27)(28)(29)(30)(31)(32)(33); very high stress (34-40); and catastrophic stress (>41). Based on these seven categories, they were further categorized into two major categories: stress and non-stress.…”
Section: Methodsmentioning
confidence: 99%
“…Overnutrition at each period of the life cycle has an adverse impact as a risk of several noncommunicable diseases (NCD) such as diabetes mellitus, hypertension, heart disease, stroke, kidney failure, and cancer. In the study of Utami et al (2020), it was stated that respondents who were obese based and visceral fat tended to have higher blood pressure. Moreover, it was found that a higher BMI affected the incidence of type II diabetes mellitus (Isnaini & Ratnasari, 2018).…”
Section: Introductionmentioning
confidence: 99%